An experimental study on the impact resistance of a new three-wave beam steel guardrail - Guo, Kai; Wang, Chenghu; Shen, Linlin (Frontiers in Materials, 2022)
It is crucial to examine the impact resistance of W-beam guardrails on both sides of the highway in order to limit the severity of impact incidents and safeguard passengers. Given its importance, this paper investigates the impact resistance of the new three-wave steel guardrail. To be specific, the study uses ANSYS to establish the vehicle impact barrier model in which the guardrail is embedded in concrete and soil column. The new accurate model of three wave beam guardrail collision stimulates the deformation degree of guardrail under the impact of vehicles with different mass and speed. According to the simulation analysis's findings, the guardrail with the post embedded in the concrete had a maximum displacement of 568.48 mm, which was less than the specification's maximum dynamic deformation of 750 mm and met the requirements for Grade 8 protection. In contrast, the guardrail with the post embedded in the soil had a maximum displacement of 679.466 mm, which was less than the specification's maximum dynamic deformation of 750 mm.